2020
DOI: 10.1080/2162402x.2020.1773204
|View full text |Cite
|
Sign up to set email alerts
|

Tumor stem cells fuse with monocytes to form highly invasive tumor-hybrid cells

Abstract: The 'cancer cell fusion' theory is controversial due to the lack of methods available to identify hybrid cells and to follow the phenomenon in patients. However, it seems to be one of the best explanations for both the origin and metastasis of primary tumors. Herein, we co-cultured lung cancer stem cells with human monocytes and analyzed the dynamics and properties of tumor-hybrid cells (THC), as well as the molecular mechanisms beneath this fusion process by several techniques: electron-microscopy, karyotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 58 publications
9
61
0
Order By: Relevance
“…It has also been published that the fusion of myeloid cells with CSC promotes metastasis in lung cancer. These hybrid cells escape the immune system and are capable of colonizing distal organs [ 82 ]. This phenomenon could be favoring the presence of CD45+ cells in the CTC enriched samples, which would explain its contribution to culture success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been published that the fusion of myeloid cells with CSC promotes metastasis in lung cancer. These hybrid cells escape the immune system and are capable of colonizing distal organs [ 82 ]. This phenomenon could be favoring the presence of CD45+ cells in the CTC enriched samples, which would explain its contribution to culture success.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon could be favoring the presence of CD45+ cells in the CTC enriched samples, which would explain its contribution to culture success. Besides, in the same work, Aguirre and colleagues have seen that this fusion depends mainly on the expression of CD36 in CSCs since it is capable of adapting tumor cells to microenvironmental conditions, especially related to energy supply [ 82 ]. We have seen an overexpression of CD36 in the CTCs after culture.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Gast et al characterized the phenotypic hybrid nature of in vitro derived CHCs. Conveniently these hybrids co-expressed nuclear RFP and cytoplasmic YFP facilitating their differentiation from the MCF7-GFP cells by ow cytometry [12]. To optimize conditions for hybrid cell enrichment, cancer cells were diluted in DEP buffer at 1x10 7 /mL and only 1x10 6 cells were loaded into the micro uidic DEP sorting device for each parameter.…”
Section: Resultsmentioning
confidence: 99%
“…In the past 5 years, other promising types of unconventional circulating neoplastic cells have been described such as tumor hybrid cells (THC) and circulating hybrid cells (CHCs) [12], [13]. CHCs are described as having hybrid phenotypes of a neoplastic cell and a leukocyte with dual expression of CD45 and tumor markers such as EpCAM or CK [10], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, apoptotic cells did not directly fuse with the healthy myoblasts, but rather induced a contact-dependent signaling with neighbors to promote fusion among the healthy myoblasts [64]. Likewise, the PS receptor CD36 facilitates the fusion of myoblasts [66], macrophages [67], and cancer cells [68]. Data from Verma and colleagues revealed that the inhibition of TMEM16 PLSases or the perturbation of the expression or activity of annexins A1 and A5 markedly impaired the fusion between osteoclast precursors, suggesting that PS exposure played a role in the membrane remodeling stages of cell fusion [62].…”
Section: Cell Fusion In Generalmentioning
confidence: 99%